Indications, Results And Complications Of Flexible Bronchoscopy In The Intensive Care Unit Of Fundacion Valle Del Lili, A University Hospital Of Reference In Latin America (2016)
In the present, the flexible bronchoscopy (FB) has become the procedure of election to explore the airways fue to its diagnostic and therapeutic capacity in pulmonary pathology. In the critically ill patient this tool gains advantage since it provides the availability of being used at the bedside with few complications. In this study we describe the indications, results and complications associated to the performance of FB in the Intensive Care Unit of Fundación Valle del Lili, a University Hospital Reference in Cali, Colombia during 2013.